Primary care and suicidality among psychiatric outpatients: The patient-doctor relationship matters. (May 2021) - Schultz, Krista; Sandhu, Sharan; Kealy, David
Objective: The purpose of the current study is to examine the relationship between the quality of the Patient-Doctor Relationship and suicidality among patients seeking mental health care; specifically, whether patients who perceive having a more positive relationship with primary care physician will have lower levels of suicidality. Method: Cross-sectional population-based study in Greater Vancouver, Canada. One-hundred ninety-seven participants were recruited from three Mental Health Clinics who reported having a primary care physician. Participants completed a survey containing questions regarding items assessing quality of Patient-Doctor Relationship, general psychiatric distress (K10), borderline personality disorder, and suicidality (Suicidal Behaviours Questionnaire-Revised-SBQ-R). Zero-order correlations were computed to evaluate relationships between study variables. Hierarchical regression analysis was used to control for confounding variables. Results: The quality of the patient doctor relationship was significantly negatively associated with suicidality. The association between the quality of the patient-doctor relationship and suicidality remained significant even after controlling for the effects of psychiatric symptom distress and borderline personality disorder features. Conclusions: The degree to which patients' perceive their primary care physician as understanding, reliable, and dedicated, is associated with a reduction in suicidal behaviors. Further research is needed to better explicate the mechanisms of this relationship over time.